2014
DOI: 10.1002/ps.3897
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing next-generation sequencing to study homeologous polymorphisms and herbicide-resistance-endowing mutations inPoa annuaacetolactate synthase genes

Abstract: In this study we have demonstrated the use of NGS data to study homeologous polymorphisms, parentage and herbicide resistance in an allotetraploid weed species, P. annua. Complete coding sequences of the ALS gene were assembled for P. infirma, P. supina, infirma-homeolog and supina-homeolog in P. annua. A pipeline consisting of read mapping, SNP calling and allele frequency calculation was developed to study the parentage of P. annua, which provided a new perspective on this topic besides the views of morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In the current study, we were able to detect two distinct gene homeologs encoding for ALS proteins (ALSa (KT346395) and ALSb (KT346396)) with a coding sequence identity of 96.2 and 98.0 % (Supplementary Information, Figure S2). When comparing our sequences to the recently published transcript sequence assemblies for Poa supina and Poa infirma (Chen et al 2015 ), it was found that ALSa originated from Poa supina and ALSb originated from Poa infirma . Heterozygosity was detected for both ALS genes within our POAAN-R3 population with individual plants having two different expressed alleles of ALSa and ALSb, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…In the current study, we were able to detect two distinct gene homeologs encoding for ALS proteins (ALSa (KT346395) and ALSb (KT346396)) with a coding sequence identity of 96.2 and 98.0 % (Supplementary Information, Figure S2). When comparing our sequences to the recently published transcript sequence assemblies for Poa supina and Poa infirma (Chen et al 2015 ), it was found that ALSa originated from Poa supina and ALSb originated from Poa infirma . Heterozygosity was detected for both ALS genes within our POAAN-R3 population with individual plants having two different expressed alleles of ALSa and ALSb, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…Recent phylogenetic analyses of Poa species showed that different amplicons of nuclear genes ( trx , CDO504, and ribosomal ITS) from P. annua were classified into two distinct clusters with P. infirma and P. supina (Soreng et al, 2010; Mao and Huff, 2012). Also, in our recent work, two homeologs of acetolactate synthase (ALS) gene were amplified from P. annua using two sets of homeolog‐specific primers and grouped with P. infirma or P. supina ALS genes (Chen et al, 2015b). Two distinct clusters in P. annua ALS sequences provides further evidence that P. annua is not autotetraploid.…”
Section: Resultsmentioning
confidence: 99%
“…The Pro197 and Ala205 mutations have been known to endow resistance to a number of sulfonylurea herbicides in annual bluegrass; however, the diversity of cross‐resistance endowed by the Trp574 mutation contributes to its evolutionary importance to the weed (Bernasconi et al., 1995; Brosnan et al., 2016; Guttieri et al., 1992; McElroy et al., 2013). It is unknown why there were difficulties in amplifying the 5′ end of ALS in P. annua , as previously published methods were utilized (S. Chen et al., 2015). The only solution now is to conduct transcriptome sequencing; however, this would be prohibitively expensive for the remaining populations.…”
Section: Discussionmentioning
confidence: 99%